Uji Aktifitas Tabir Surya Dan Stabilitas Fisik Formula Gel Semprot Dari Ekstrak Temugiring (Curcuma Heyneana Val.) Dan Ekstrak Kayu Manis (Cinnamomum Burmanii Nees.) Dengan Kombinasi Karbopol Dan HPMC. - Youstiana Dwi Rusita; Suhendriyo Suhendriyo (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Spray Gels, Sunscreens, Physical Stability, Rhizome Temugiring And Cortex Kayumanis. Excessive sun exposure can harm human skin, for skin damage can occur after exposure, namely in the form of burning or skin Erythema which is the onset of symptoms of degradation of cells and tissues. Sunscreen preparations have benefits to protect skin from exposure to ultraviolet rays and also contains antioxidants. Cinnamon (Cinnamomum burmanni Nees.) that has the activity of sunscreen, because it contains the compound sinamaldehid in addition also have activity as antioxidant. Rhizome temugiring (Curcuma Heyneana Val.) contain a flavanoid with fairly high antioxidant activity. Preparation of the gel has a number of advantages including not sticky and gels have a steady flow of tiksotropik and pseudoplastik i.e. solid gel when it is stored and will soon melt away when beaten. Spray technique is one of the new material has advantages which allow preparations sprayed with the dispersed evenly without needing to contact directly to flatten. Base that is often used in the making of gel karbopol and HPMC, among others. This type of Research design is a True Experiment. The formula that is used, there are three types with a combination of karbopol and HPMC. The research of spray gel extract kayumanis and extract temugiring on physical organoleptic stability Formula I red the typical smell of condensed form, kayumanis, part or a little murky, there are some air bubbles and cool on the skin when sprayed. Formula II, color of red brick the distinctive aroma preparations kayumanis, condensed form, no turbid and slightly cold when air bubbles, didispersikan to the skin; Test the viscosity Formula I 4000mPas, Formula II 1000 mPas, Formula III 1500mPas; Power test scatterplot latched into a Formula I attached did not drip to the formulation II is slightly attached and dripping, Formula III wasn't too attached to or flow; Test the spray pattern, the Formula I and II pattern that is formed is not round spread, Formula III pattern formed round spread; Its homogeneity test Formulation I, II, and III there are no particles; Irritation test Formulation I, II, and III the absence of symptoms of irritation. As for testing the stability of the antioxidant Formula I average IC50 values 1.21 SPF value average value, Formula II 10.48 IC50 value of 1.23 average average SPF 19.29, Formula III average IC50 values 1.18 SPF value average 12.51. Each formula no different IC50 values activity and SPF with the combination of karbopol and HPMC. Physical stability test and a good antioxidant formula III is with a combination of Karbopol 50% and 50% HPMC